Developing University Science and Technology Company in Vietnamese Public Universities - Hoang Anh, Mai (VNU JOURNAL OF ECONOMICS AND BUSINESS; Vol 36 No 4, 2020)
This research focus on current situation of university spin-off company in public university in Vietnam to analysis the reason of limitation and propose some proposal to develop the university spin-off company. In the scope of this research, author focus on the university spin-off company in famous university in Hanoi to find out the problems of this model. Beside the secondary data, author used indepth interview with experts who are the leaders of these univerisy to deeply understand the problem of these model. The interview results and the previous research, author indicates ten objective reasons and two subjective reasons of government-based organization. Some policies proposal and strategy for developing university spin-off company in public university.